The kinetics of polyacrylamide adsorption on polycrystalline gold - Čamovska, Dragica B. (Array, 2008)
Abstract: Fast potential step measurements (0.9 ® 1.9 ® 0.9 V, E vs. she) with simultaneous monitoring of the double layer capacity were applied in the study of the kinetics of PAA adsorption on gold from 0.5 M H2SO4, at 293 K. It was shown that the addition of PAA to the solution at 1.9 V (in the presence of a very thin oxide layer at the gold surface of 1 nm) does not affect the value of the capacity of the Au/Au2O3/PAA-solution interface, which was also confirmed by Electrochemical Impedance Spectroscopy. After the very fast cathodic reduction of the thin oxide layer (step 1.9 ® 0.9 V) for several milliseconds, the initial adsorption of PAA molecules at the bare gold surface reappeared in approx. 10 ms, causing exhaustion of the metal/solution boundary layer. The induction region (dq/dt = 0) as well as the diffusion controlled region (dq/dt = const. = f Mn((PAA); cPAA) are characteristic of low concentrations in the solution. According to the experimentally obtained linear parts of the (q / logt)-dependences, values of the diffusion coefficient of PAA-molecules with different molecular weights were calculated. These values follow fairly well the empirical equation: DPAA = 7.03 × 10–4 Mn–0.66 cm2 s–1. Using the same procedure, the diffusion coefficient of 9 × 10–6 cm2 s–1 for adsorption of »small« organic molecules, such as HMBT, was calculated